Effects of a microbial preparation, a probiotic and commercial antibiotic on the productive performance and pigs health in post-weaning period - Flores, Luis; Elías, Arabel; Proaño, F.; Granizo, G.; Medina, Yolaine; López, Sandra; Herrera, F.; Caicedo, William (Cuban Journal of Agricultural Science, 2016)
To measure the influence of a Stafac (Virginiamycin at 2%, 1 kg.t-1) commercial antibiotic, a ML 100 E (1kg.t-1) commercial probiotic and a (15 mL.kg LW -1) microbial preparation in the productive performance and health of post weaning pigs, an experiment by a complete randomized design, with three treatments and four repetitions was conducted. A total of 120 barrow pigs were used, from Landrace x Large White cross, with Belga x Pietrain sire at finishing stage, of 28d of age, 6.85 kg average weight and ± 0.25 kg. In pigs feed concentrates to those that the microbial preparation was added, the higher final weight and the best gain of total weight and daily (P < 0.05): 25.85 kg, 18.97 kg and 440.75 g was determined, respectively. The most efficient values, as feed conversion, protein and energy, were obtained in the treatment to which the microbial preparation 1.66 kg DM.kg LW-1, 347.35 g.kg LW-1 of CP and 22.71 MJ.kg LW-1 was added, respectively. The less digestive problems presence (number of diarrhea) was registered in the group of animals fed with concentrate plus microbial preparation, with incidence of 13.With the addition of the microbial preparation, at 15 mL.kg LW-1,it can improve the concentrates nutritional quality and obtain better productive and health parameters in post-weaning pigs, without using antibiotics. Key words: microbial preparation, commercial antibiotic, postweaning pigs, whey